2020
DOI: 10.1186/s12943-020-01196-4
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circBFAR promotes the progression of pancreatic ductal adenocarcinoma via the miR-34b-5p/MET/Akt axis

Abstract: Background: Accumulating evidence suggests that circular RNAs (circRNAs) are important participants in cancer progression. However, the biological processes and underlying mechanisms of circRNAs in pancreatic ductal adenocarcinoma (PDAC) are unclear. Method: CircRNAs were verified by Sanger sequencing. Colony formation, 5-Ethynyl-2′-deoxyuridine (EdU), and Transwell assays were performed to investigate the effect of circBFAR on the proliferation, invasion, and migration of PDAC cells in vitro. RNA pull-down as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 46 publications
2
81
0
2
Order By: Relevance
“…13,14 Accumulating studies have reported that circRNAs are widely detected in a variety of cancers and play an indispensable regulatory role in tumor development and progression. 15,16 Herein, we report a novel circRNA, circEHBP1 (hsa_circ_0005552), which was markedly upregulated in BCa and correlated positively with the prognosis of patients with BCa. circEHBP1 overexpression induced lymphangiogenesis and LN metastasis of BCa in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Accumulating studies have reported that circRNAs are widely detected in a variety of cancers and play an indispensable regulatory role in tumor development and progression. 15,16 Herein, we report a novel circRNA, circEHBP1 (hsa_circ_0005552), which was markedly upregulated in BCa and correlated positively with the prognosis of patients with BCa. circEHBP1 overexpression induced lymphangiogenesis and LN metastasis of BCa in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, upregulated circ_0030235 facilitates PDAC cell growth and migratory and invasive potential, partly by inhibiting and sponging miR-1253 and miR-1294 [ 21 ]. Highly expressed circBFAR is also correlated with the poorer prognosis of patients with PDAC and promoted the progression of PDAC cells by sponging miR-34b-5p to activate the mesenchymal-epithelial transition factor (MET)/PI3K/Akt signaling pathway [ 22 ]. Hence, the evidence has been obtained to support the clinical significance of investigating the functional roles of circRNAs in PDAC and many circRNAs remain to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Successfully accomplishing multi-omics data integration by systems biology approaches will fulfill future expectations and the need for robust, accurate, and feasible biomarker panels for pancreatic cancer. [166] Tumor tissue hsa_circ_0006215 Upregulated circRNA overexpression [167] Tumor tissue, plasma exosome circ-IARS Upregulated circRNA overexpression [168] Tumor tissue circ-PDE8A Upregulated circRNA overexpression [169] Tumor tissue/cell hsa_circ_0001649 Downregulated Microarray/qRT-PCR [170] Tumor tissue/cell hsa_circ_0005397 (circ-RHOT1) Upregulated Microarray/qRT-PCR [171] Tumor tissue/cell lines hsa_circ_0030235 Upregulated circRNA overexpression [172] Tumor tissue/cell lines hsa_circ_0007534 Upregulated circRNA overexpression [173] Tumor tissue/cell lines ciRS-7 (Cdr1as) Upregulated qRT-PCR [174] Tumor tissue hsa_circ_0007334 Upregulated Microarray/qRT-PCR [175] Tumor tissue circLDLRAD3 Upregulated circRNA knockdown [176] Tumor tissue/cell circASH2L Upregulated Microarray/qRT-PCR [177] Tumor tissue/cell lines circADAM9 Upregulated circRNA knockdown [178] Tumor tissue/cell hsa_circ_001653 Upregulated circRNA knockdown [179] Tumor tissue/cell circHIPK3 Upregulated circRNA knockdown [180] Tumor tissue/cell circFOXK2 Upregulated circRNA knockdown [181] Tumor tissue hsa_circ_0009065 (circBFAR) Upregulated circRNA overexpression [70] Tumor tissue hsa_circ_0086375 (circNFIB1) Downregulated circRNA knockdown [182] Tumor tissue/cell hsa_circ_0013912 Upregulated circRNA overexpression [183] Tumor tissue/cell lines hsa_circ_001587 Downregulated circRNA knockdown [184] Tumor [194] Tumor tissue BC008363 Upregulated Microarray/qRT-PCR [195] Tumor tissue HSATII Upregulated RNA-seq [196] Serum/plasma U2snRNA Upregulated Microarray/qRT-PCR [197] Pancreatic * CZE: capillary zone electrophoresis, ELISA: enzyme-linked immunosorbent assay, ELLA: Enzyme-linked lectin assay, FISH: fluorescence in situ hybridization, GC: gas chromatography, HILIC: Hydrophilic interaction chromatography, HRMAS: high-resolution magic angle spinning, LC: liquid chromatography, MS: mass spectrometry, NMR: nuclear magnetic resonance, qRT-PCR: quantitative reverse transcription polymerase chain reaction, TOF: time of flight, WB: Western blot, WES: Whole exome sequencing, WGS: whole genome ...…”
Section: Resultsmentioning
confidence: 99%